2013
DOI: 10.1016/j.ejmg.2013.05.005
|View full text |Cite
|
Sign up to set email alerts
|

HUWE1 mutation explains phenotypic severity in a case of familial idiopathic intellectual disability

Abstract: a b s t r a c tThe advent of next-generation sequencing has proven to be a key force in the identification of new genes associated with intellectual disability. In this study, high-throughput sequencing of the coding regions of the X-chromosome led to the identification of a missense variant in the HUWE1 gene. The same variant has been reported before by Froyen et al. (2008). We compare the phenotypes and demonstrate that, in the present family, the HUWE1 mutation segregates with the more severe ID phenotypes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 18 publications
(19 reference statements)
2
9
0
1
Order By: Relevance
“…Its dysregulation leads to various movement disturbances, dementia and hypogonadotropic hypogonadism [44,45]. Thus, it is not surprising that a growing group of ID proteins are directly involved in UPS-mediated protein degradation, such as UBE3A [46] [47], UBE2A [48,49,50,51], UBE3B [52,47], HUWE1 [53,54,55], MID1 [56][57][58][59], CUL4B [60,[61][62][63], UBR1 [64,65,66], TRIP12 [67][68][69], and RNF216 [45,[70][71][72].…”
Section: Discussionmentioning
confidence: 99%
“…Its dysregulation leads to various movement disturbances, dementia and hypogonadotropic hypogonadism [44,45]. Thus, it is not surprising that a growing group of ID proteins are directly involved in UPS-mediated protein degradation, such as UBE3A [46] [47], UBE2A [48,49,50,51], UBE3B [52,47], HUWE1 [53,54,55], MID1 [56][57][58][59], CUL4B [60,[61][62][63], UBR1 [64,65,66], TRIP12 [67][68][69], and RNF216 [45,[70][71][72].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed a crucial role of the UPS in the spatial and temporal control of protein turnover in the nervous system, which regulates the development and maintenance of specialized neuronal structures, and consequently , neuronal transmission. Thus, it is not surprising that a growing group of ID linked proteins are directly involved in UPS-mediated protein degradation such as UBE3A, UBE2A, UBE3B, HUWE1, MID1, CUL4B, and UBR1 (Badura-Stronka et al, 2010; Basel-Vanagaite et al, 2012; Budny et al, 2010; Flex et al, 2013; Froyen et al, 2008; Hwang et al, 2011; Isrie et al, 2013; Kishino et al, 1997; Matsuura et al, 1997; Nascimento et al, 2006; Tarpey et al, 2007; Zenker et al, 2005; Zou et al, 2007). …”
Section: Genes Linked To Id and Asdmentioning
confidence: 99%
“…Increased copies of HUWE1 are associated with non-syndromic intellectual disability (Friez et al, 2016 #922; Froyen et al, 2012; Froyen et al, 2008; Madrigal et al, 2007). Missense mutations in HUWE1 occur in multiple families with intellectual disability, including families with Juberg-Marsidi-Brooks syndrome (Friez et al, 2016; Froyen et al, 2008; Isrie et al, 2013). This suggests both increased and decreased HUWE1 function could be associated with intellectual disability, but evidence from an in vivo model system supporting or refuting this possibility remains absent.…”
Section: Introductionmentioning
confidence: 99%